Income Distribution, Value Judgments, and Welfare: Errata - Fisher, F. M. (Quarterly Journal of Economics, 1957)
(1). P. 386, note, last line: Theorem 5 should not appear. (2). P. 402, second line of Theorem 5: Line should begin with “ Q ”, not “ P ”. (The theorem is correct as it stands, but is easier to interpret with the correction.) (3). P. 403, eighth line from bottom: “= ( &Ymacr; + δ*)” should be deleted. (4). P. 421, Theorem A , second line and Corollary A , second line: “∽” should be “<f><inline-fig> </inline-fig></f>”.